Implementasi Quality Function Deployment (QFD) pada Produk Susu Kedelai - Puspitasari, Diana; Wedowati, Endang Retno; Min, Yosefina Theodesia (Universitas Trunojoyo Madura, 2009)
Soya milk is healthy drink, and high nutrition such as protein, lowfat, carbohidrat, calsium, phosplior, iron, and vitamin. Besides that soya milk also cheaper than cow milk. But market of soya milk can not be expanse. Based on that reason needed toJznd solution to improve market of soya milk. Solution can be started from voice of customer. Research for the voice of customer can be use Quality Function Deployment (QFD) method. By this method in this research we can understand what customer want. Customer of soya milk want fit volume and good packaging beside low price or we can say low price with hzgh quality. It can be start from improve nutrition, packaging, flavour, volume, price, taste, and performance produk as atribut-atribut base on voice of customer.Keyword: soya milk, Quality Function Deployment, voice of cuatomer.